Orientalism in Sport: Analyzing The Western Representation of Islam at FIFA World Cup Qatar 2022 - Ibrahim, Faris (Lembaga Penelitian Universitas YARSI, 2025)
This article aims to critically read orientalism as a tool to represent the East and Islam at the 2022 World Cup in Qatar. The article argues that sport, in this case football, which is often considered neutral from interests as it has been used by the United Nations (UN) as a means to campaign for growth and peace in 2013, now faces several challenges in the form of biased Western interests towards the Eastern world, and what happened at the 2022 Qatar World Cup is a clear illustration of this conflict of interest. By utilizing virtual ethnography, and case study methods, this article finds that: first, the narrative of orientalism is still strong and even spreads to all realms of life, including sports. Second: more than a conflict of political interests, what happened in the Qatar World Cup was actually a clash of values that had been going on for a long time. Thirdly, Western media plays an important role in representing the image of the East and Islam in a biased way in covering what happened at the Qatar 2022 World Cup.